Domestic violence against women: a crossectional study in rural area of Amravati district of Maharashtra, India - Jawarkar, Ajay K.; Shemar, Himani; Wasnik, Vinod R.; Chavan, Manisha S. (International Journal of Research in Medical Sciences, 2017)
Background: Domestic violence against women is a matter of serious public health concern in most of the communities and culture. In India, the problem has been highlighted after legislation against domestic violence in 2005, popularly known as the protection of women from domestic violence act. Main objectives of the study were to assess the prevalence of domestic violence against women, to study the sociodemographic factors in females suffering from domestic violence and to identify causes of domestic violence in them. Methods: A crossectional study was carried in the field practice area of rural health training centre of Dr. Panjabrao Deshmukh Memorial Medical College, Nerpinglai in Amravati district of Maharashtra state for a period of 3 months. Simple random sampling method was used for the selection of samples. The study participants were interviewed using a predesigned pretested questionnaire. Proportion, Chi square test were calculated for the analysis of the study. Results: Out of 400 study participants interviewed, 161 (40.25%) reported some type of violence i.e. either in the form of physical, emotional or sexual violence in their life time or in recent past. The most common type of violence reported was physical violence. The most common cause of domestic violence reported in our study was financial problems followed by influence under alcohol. Conclusions: The prevalence of domestic violence was 40.25% which is still high and necessary measures should be taken to strengthen the laws for women and to empower them.